Pengaruh Penggunaan Gadget Terhadap Kemampuan Interaksi Sosial Siswa Kelas V SDN 2 Tallunglipu (Jurnal Keguruan dan Ilmu Pendidikan, 2021)
The goal of this study was to determine the effect of the use of gadgets on the social interaction skills of 5th graders. This study used a quantitative approach with survey research type. The data collection techniques used were interviews, questionnaires and documentation. The data analysis technique used was the product-moment correlation analysis. The sample of respondents in this study were 20 students consisting of 8 males and 12 females. Based on the research findings, the coefficient of gadget use is 4.273, while can be calculated in the table with ? = 0.05 and df = 18 (obtained from the n-2 formula, where n is the number of respondents, that is 20-2) so that is 2,100. The gadget usage variable has a significant level of 000 < 0.05, which means that it is significant with H1 accepted and H0 rejected. Thus, it can be concluded that there is a significant influence between the use of gadgets and students' social interactions.